Right-handed spiral chiral organic metal halide, preparation method thereof and application of right-handed spiral chiral organic metal halide as linear polarization luminescent material
By self-assembly preparing one-dimensional right-hand spiral chiral organometallic halide material in thermal saturated solvent, the problems of low luminescence efficiency and poor stability of existing linear polarization emitting materials are solved, and efficient, adjustable and stable linear polarization luminescence is achieved. Performance, suitable for a variety of optoelectronic applications.
Patent Information
- Application Number
- CN202411375142.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing linear polarization emitting materials have problems such as limited luminous efficiency, poor stability, difficulty in achieving wide spectrum regulation and poor processability, and are difficult to meet the needs of high-precision display and communication technology.
By introducing the asymmetric organophosphine ligand diphenyl-2-pyridine phosphine, self-assembled with sodium dicyanamide and cuprous halide in a thermally saturated solvent, a one-dimensional right-hand spiral hand with excellent linear polarization luminescent characteristics was prepared. organic metal halide material.
It has achieved a photoluminescence quantum yield of up to 48.22%, linear polarization ratio of up to 1.77, and has shown good thermal stability and weather resistance. It is suitable for various optoelectronic applications such as high-end anti-counterfeiting, quantum communication and photonic devices.
Smart Images

Figure CN119431445A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a right-handed helical chiral organic metal halide and a preparation method thereof and application thereof as a linearly polarized luminescent material, belonging to the technical field of optoelectronic materials. Background Art
[0002] In modern high-precision display and communication technologies, the luminescent properties of traditional luminescent materials often lack directionality and are difficult to meet the needs of specific optoelectronic functions. Linearly polarized luminescent materials can not only emit light, but also perform optical modulation, which means that they can control the direction and polarization state of light, thereby improving the efficiency and quality of display and communication. Therefore, they have broad application value. For example, in the field of display technology, linearly polarized luminescent materials can be used to improve the brightness and contrast of display devices, while reducing light reflection, thereby improving display effects. In the field of optical communications, linearly polarized luminescent materials can be used to manufacture polarized light sources, which is particularly important for polarization mode splitting multiplexing technology, which can improve the capacity and efficiency of communication systems.
[0003] Although linearly polarized emission materials have significant application potential in optoelectronic devices, there are also some technical bottlenecks and challenges. For example, existing organic small molecules, organic polymers, inorganic nanomaterials, and polymer liquid crystals have more or less disadvantages such as limited luminous efficiency, poor stability, difficulty in achieving wide spectrum control, and poor processability.
[0004] Through in-depth research on the molecular structure, orientation and luminescence mechanism of materials, the development of high-performance linearly polarized luminescent materials will greatly promote the development of next-generation optoelectronic technology. Future research should be carried out in depth in terms of material design, performance optimization and device application to meet the diverse needs of industry and scientific research. Summary of the invention
[0005] In order to solve the problem of lack of directionality in the luminescence characteristics of traditional materials in the prior art of high-precision display and communication technology and the aforementioned performance and processing disadvantages of linearly polarized emission materials, the present application provides a right-handed helical chiral organic metal halide, which is self-assembled with sodium dicyanamide and cuprous halide in a hot saturated solvent by introducing an asymmetric organic phosphine ligand diphenyl-2-pyridylphosphine, and successfully prepares a one-dimensional right-handed helical chiral organic metal halide material with excellent linear polarized luminescence characteristics. Organic metal halides are self-assembled from organic and inorganic components, which can effectively solve these problems, thereby providing a new type of efficient, controllable and stable luminescent material system that can solve the disadvantages of limited luminescence efficiency, poor stability, difficulty in achieving wide spectrum control, and poor processability.
[0006] This application adopts the following technical solutions:
[0007] According to one aspect of the present application, a right-handed helical chiral organic metal halide is provided, wherein the chemical formula of the right-handed helical chiral organic metal halide is [(PN)2Cu2(dca)X] n ;
[0008] Wherein, PN is an asymmetric organic phosphine ligand, dca is a dicyanamide anion, and X is a halogen ion.
[0009] There is a strong coordination effect between the Cu ions and the DCA anions in this material, which improves the luminescence efficiency and electron transfer ability through the π conjugation effect.
[0010] Optionally, the right-handed helical chiral organometallic halide is obtained by self-assembly of an asymmetric organophosphine ligand, a dicyanamide salt, and cuprous halide in a hot saturated solvent.
[0011] Optionally, the right-handed helical chiral organometallic halide is synthesized by self-assembly of diphenyl-2-pyridinephosphine ligand (PN), sodium dicyanamide (Na(dca)) and cuprous chloride (CuCl), has an orthorhombic crystal structure, a space group of Pna21, and exhibits a helical chiral structure.
[0012] Optionally, the right-handed helical chiral organometallic halide has an orthorhombic crystal structure and a space group of Pna21, and has a one-dimensional chain-like helical chiral structure.
[0013] Optionally, in the crystal structure of the right-handed helical chiral organometallic halide, Cu1 and Cu2 ions are bridged by halogen ions to form a binuclear metal cluster, and Cu ions are coordinated with asymmetric organophosphine ligands and dicyanamide anions to form a distorted trigonal bipyramidal structure.
[0014] Optionally, X is selected from Cl - Br - ,I - By introducing different halogens (such as Br, I), the material can be further expanded to [(PN)2Cu2(dca)Br]n and [(PN)2Cu2(dca)I] n , still maintaining the spiral chiral structure, the luminescence performance and linear polarization characteristics have changed.
[0015] Optionally, the right-handed helical chiral organic metal halide has a linear polarization luminescence characteristic, and the polarization ratio is 1.77. The rotation angle of the linear polarizer and the luminescence intensity are in a sin2θ relationship, showing a highly ordered optical orientation.
[0016] Optionally, the right-handed helical chiral organic metal halide has an emission wavelength in the range of 575 nm to 625 nm within an excitation wavelength range of 250 nm to 420 nm, and exhibits a red shift as the excitation wavelength increases.
[0017] The photoluminescence quantum yield of the material is 48.22%. Under 360nm excitation, the emission wavelength of the material is 598nm, and the photoluminescence thereof shows a relatively stable shape and intensity in the range of 250nm to 420nm, and the emission spectrum covers the orange-yellow to orange-red region.
[0018] Optionally, the thermal weight loss temperature of the right-handed helical chiral organometallic halide is greater than or equal to 372° C., and the phase transition temperature is greater than or equal to 219° C. The material has excellent thermal stability, has no significant weight loss below 372° C., exhibits phase transition behavior at 219° C., and has good environmental stability.
[0019] According to another aspect of the present application, there is provided a method for preparing the above-mentioned right-handed helical chiral organometallic halide, comprising the following steps:
[0020] A mixture containing an asymmetric organic phosphine ligand, dicyanamide salt and cuprous halide is added to a hot saturated solvent and mixed evenly, and the right-handed helical chiral organic metal halide is obtained by heating to dissolve, cooling and precipitation self-assembly.
[0021] Optionally, a method for preparing a right-handed helical chiral organic metal halide comprises the following steps: mixing a diphenyl-2-pyridinephosphine ligand, sodium dicyanamide and cuprous chloride in a hot saturated solvent, dissolving them by heating, and self-assembling after cooling to obtain a right-handed helical chiral organic metal halide single crystal material.
[0022] Optionally, the asymmetric organic phosphine ligand is selected from diphenyl-2-pyridylphosphine ligands.
[0023] Optionally, the dicyanamide salt is selected from sodium dicyanamide.
[0024] Optionally, the cuprous halide is selected from at least one of cuprous chloride, cuprous bromide and cuprous iodide.
[0025] Optionally, the hot saturated solvent is selected from a mixed solution of DMF and acetonitrile.
[0026] Optionally, the molar ratio of the organic phosphine ligand, dicyanamide salt and cuprous halide is 1:(0.4-0.6):(0.8-1.2).
[0027] Optionally, the conditions for heating and dissolving include: under vacuum or anaerobic conditions, the heating temperature is 120-130° C., and the heating time is 30-60 min.
[0028] Optionally, the self-assembly time is 18 to 36 hours.
[0029] According to another aspect of the present application, there is also provided an application of the above-mentioned right-handed helical chiral organic metal halide as a linearly polarized luminescent material in optoelectronic fields such as high-end anti-counterfeiting, quantum communication and photonic devices.
[0030] Optionally, the application includes: regulating the polarization emission direction through optoelectronic devices to improve the contrast and clarity of the display effect. The rotation angle of the linear polarizer is in a sin2θ relationship with the luminous intensity, showing a highly ordered optical orientation.
[0031] The beneficial effects of this application include:
[0032] The present application provides a right-handed helical chiral organic metal halide having a photoluminescence quantum yield of up to 48.22%, a linear polarization ratio of up to 1.77, and exhibiting good thermal stability and weather resistance, and is particularly suitable for a variety of optoelectronic applications such as high-end anti-counterfeiting, quantum communications, and photonic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The compound of the present application [(PN)2Cu2(dca)Cl] n 1Cu + Ion, Cl - Ion, DCA - Coordination environment diagram of anion and organic ligand PN.
[0034] Figure 2 The compound of the present application [(PN)2Cu2(dca)Cl] n 1 presents a one-dimensional chain structure of a right-handed spiral.
[0035] Figure 3 The compound of the present application [(PN)2Cu2(dca)Cl] n Powder diffraction pattern (PXRD) of 1, the black curve is the simulated PXRD pattern, and the red curve is the experimental PXRD pattern.
[0036] Figure 4 The compound of the present application [(PN)2Cu2(dca)Cl] n 1Thermogravimetric-differential scanning calorimetry-derivative thermogravimetric curve (TGA-DSC-DTG).
[0037] Figure 5 This is the solid-state photoluminescence spectrum of the compound [(PN)2Cu2(dca)Cl]n 1 of the present application, with the excitation wavelength swept from 250nm to 420nm.
[0038] Figure 6The compound of the present application [(PN)2Cu2(dca)Cl] n 1CIE 1931 color coordinates of fluorescence emission under excitation in the range of 250nm to 420nm.
[0039] Figure 7 The compound of the present application [(PN)2Cu2(dca)Cl] n The absolute fluorescence quantum yield is 1.
[0040] Figure 8 The compound of the present application [(PN)2Cu2(dca)Cl] n Chiral performance test of 1: (a) is the solid circular dichroism absorption spectrum, (b) is the linear dichroism absorption spectrum, (c) is the detector tube voltage during the test, and (d) is the solid-state UV-visible absorption spectrum.
[0041] Fig. 9 After rotating 90 degrees for this application, the compound [(PN)2Cu2(dca)Cl] n Chiral performance test of 1: (a) is the solid circular dichroism absorption spectrum, (b) is the linear dichroism absorption spectrum, (c) is the detector tube voltage during the test, and (d) is the solid-state UV-visible absorption spectrum.
[0042] Fig.10 The compound of the present application [(PN)2Cu2(dca)Cl] n 1 Linearly polarized emission spectrum of emission intensity, emission position and emission peak shape between 0 and 90°.
[0043] Fig.11 The compound of the present application [(PN)2Cu2(dca)Cl] n 1 Linearly polarized emission spectrum of emission intensity, emission position and emission peak shape between 100 and 180°.
[0044] Fig.12 The compound of the present application [(PN)2Cu2(dca)Cl] n 1 as a function of the rotation angle of the linear polarizer. DETAILED DESCRIPTION
[0045] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0046] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0047] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0048] Example 1
[0049] Preparation of right-handed helical chiral organometallic halides: Turn on the electronic balance and preheat for 30 minutes; weigh 2mmol of organic ligand diphenyl-2-pyridinephosphine (about 526mg), 1mmol of sodium dicyanamide (about 90mg), and 2mmol of CuCl (about 200mg) in turn; transfer to a 250mL flat-bottom round-bottom flask, then add a magnetic stirrer, 24mL of anhydrous DMF and 4mL of CH3CN; evacuate through a 90° exhaust joint, and repeat three times. Heat at 125°C in anoxic conditions for 45 minutes, at which point the reaction system appears as a dark yellow turbid liquid; filter while hot; the filtrate evaporates slowly at room temperature after cooling. After about 1d, yellow single crystals will precipitate from the clear yellow solution. Enrich the yellow single crystals, wash with hot DMF (about 60oC), and vacuum dry to obtain the target product [(PN)2Cu2(dca)Cl] n 1, yield 44.75% (based on the organic ligand diphenyl-2-pyridinylphosphine, PN).
[0050] Test Example 1 Structural Characterization
[0051] The diffraction data of the crystals were obtained by ω scanning technique at 100K on a Rigaku FR-X 3kW X-ray single crystal diffractometer using Mo-Kα radiation. The diffraction data were restored by CrysAlisPro software and solved by the direct method using Olex2 1.2 software. All non-hydrogen atoms were obtained by Fourier synthesis, and the final structure was refined by the least squares method. All non-hydrogen atoms were anisotropically refined, and hydrogen atoms on C and N atoms were generated by theoretical hydrogenation. The crystal structure of each compound was further confirmed and verified using the PLATON program to ensure that the compound had no other symmetry or a higher symmetry space group.
[0052] The sample [(PN)2Cu2(dca)Cl] of Example 1 n 1 The X-ray powder diffraction phase analysis (XRD) after grinding was carried out on a Rigaku SmartLab multifunctional X-ray diffractometer with a Cu target and a Kα radiation source. The test results are as follows Figure 3 As shown, the compound [(PN)2Cu2(dca)Cl] n The PXRD experimental test curve of 1 matches the peak position of the curve simulated by single crystal theory, which shows that the compound [(PN)2Cu2(dca)Cl] n 1 has a higher physical purity.
[0053] X-ray powder diffraction and X-ray single crystal diffraction results show that:
[0054] Compound [(PN)2Cu2(dca)Cl] n 1 belongs to the orthorhombic crystal system, its space group is Pna21, and it has a one-dimensional molecular structure. Figure 1 As shown, in the asymmetric unit of compound 1, there are two diphenyl-2-pyridylphosphine ligands and one bridged dicyanamide DCA. - Anion, 1 bridging Cl - ions and two Cu + ions. Both Cu1 and Cu2 ions are in penta-coordinate mode: Cu1 is coordinated with two diphenyl-2-pyridine phosphine ligands (including N1 on the pyridine ring of one phosphine ligand and P2#1 on the other phosphine ligand), N3 atom on dicyanamide, Cl1 ion and Cu2, respectively, to obtain a distorted trigonal bipyramidal configuration; Cu2 is coordinated with two diphenyl-2-pyridine phosphine ligands (including P1#2 on one phosphine ligand and N2 atom on the pyridine ring of the other phosphine ligand), N4 atom on dicyanamide, Cl1#2 ion and Cu1#2, respectively, to obtain a distorted trigonal bipyramidal configuration. Among them, the coordination bond distance between Cu and N atoms is between 2.0285 (19) and 2.1554 (18), which is within a reasonable range. Between Cu1 and Cu2#1, a binuclear metal cluster structure is formed through the Cl1 atom, and the distance between Cu1 and Cu2 is
[0055] Test Example 2 Thermal Stability Test
[0056] Example 1 Compound [(PN)2Cu2(dca)Cl] prepared n The thermal stability of 1 was measured by thermogravimetric analysis (TGA) on a METTLER TOLEDO analyzer in a N2 atmosphere. The sample was heated in an Al2O3 crucible at 10K min -1 In addition, the thermogravimetric curve is processed, and its derivative thermogravimetric curve can be obtained by taking the first-order differential with respect to time. Figure 4 As shown, the compound [(PN)2Cu2(dca)Cl] n 1 has good thermal stability and there is no obvious weight loss before 372℃. However, it is worth noting that at around 219℃, the compound [(PN)2Cu2(dca)Cl] n 1 did not experience significant weight loss, but there was a significant endothermic behavior, which indicated that the compound [(PN)2Cu2(dca)Cl] n 1 There is a phase transition behavior after 219℃.
[0057] Test Example 3 Photoluminescence Performance Test
[0058] The instrument selected for the photoluminescence performance test is Edinburgh FLS1000, in which the excitation light source is a Xe lamp, and the ultraviolet light of a specific excitation band can be selected through the filtering system. The excitation slit is 1nm and the receiving slit is 1nm. The experimental spectrum of its photoluminescence is shown below Figure 5 As shown. For the sample [(PN)2Cu2(dca)Cl] prepared in Example 1 n 1. Scanning from 250nm to 420nm, the sample emits orange-yellow light, with the maximum emission peak intensity at around 598nm, and the corresponding excitation wavelength is around 360nm. As the excitation wavelength increases, the sample [(PN)2Cu2(dca)Cl] n The emission of 1 shows a red-shifted trend. What is more interesting is that with the change of excitation wavelength, its emission peak position and intensity will change slightly, showing a less obvious wavelength-dependent photoluminescence behavior, but the shape of its emission spectrum is always within the emission spectrum range under 360nm excitation. Based on the intensity and peak shape of the emission peak, a CIE 1931 color coordinate diagram of fluorescence emission under excitation from 250nm to 420nm was made, as shown in the figure below: Figure 6 As shown, it can be seen that as the excitation wavelength increases, the luminescence changes from orange-yellow emission to orange-red emission.
[0059] The quantum yield test is a test of accuracy. Simply put, the quantum yield is obtained by calculating the corresponding peak area through the emission spectra of the blank and the sample. The only requirement for the quantum yield test is accuracy, and every step of the test needs to be quantified. Every link and every detail in the test process may have a significant impact on the results. In this test, polytetrafluoroethylene was used as a blank plate. The test results are as follows Figure 7 As shown, 360nm is selected as the excitation light, and the emission scanning spectrum is 340nm~800nm. In the result spectrum of the quantum yield test, S (blank) S is the signal value of the excitation light scattered from the blank plate and entering the detector, which can intuitively reflect the cleanliness of the blank plate; (sample) It is the scattered signal emitted by the sample after the excitation light hits the sample. Generally, it is required that the luminescent sample covers the blank plate as much as possible; E (blank) E is the fluorescence background baseline, which is generally close to the noise of the detector (if the integrating sphere or the blank sample pool is contaminated, the background baseline will have an obvious fluorescence peak, so the inside of the integrating sphere and the blank sample pool should be cleaned repeatedly before testing); (sample) is the fluorescence signal emitted by the sample after the excitation light hits the sample. Therefore, the absolute fluorescence quantum yield (PLQY,η D ) is calculated as:
[0060]
[0061] According to this formula, the compound [(PN)2Cu2(dca)Cl] can be obtained. n The absolute fluorescence quantum yield of 1 is 48.22%, which is similar to the luminescence efficiency of reported CuCl-based organometallic halides.
[0062] Test Example 4 Chiral Performance Test
[0063] Since the compound [(PN)2Cu2(dca)Cl]n 1 prepared in Example 1 has a non-central space group and exhibits right-handed helical chirality at the molecular microscopic level, the compound [(PN)2Cu2(dca)Cl] n 1. Test the chiral properties, where the ground state chirality can be obtained through circular dichroism absorption spectrum (CD) or linear dichroism absorption spectrum (LD). Excited state chiral properties can be obtained through circular polarization emission spectrum and linear polarization emission spectrum.
[0064] The instrument selected for the measurement of ground state chirality is the Japanese JASCO circular dichroism spectrometer J-1500, which can perform multi-channel tests simultaneously. The advanced four-channel lock-in amplifier equipped with the instrument can collect up to four data channels simultaneously, including CD, absorbance, linear dichroism (LD), fluorescence, fluorescence detection CD (FDCD), fluorescence detection LD (FDLD) and fluorescence anisotropy. The solid-state tableting method is adopted, and the specific operation is: weigh 95 mg of spectrally pure KBr and 5 mg of sample, grind and mix them thoroughly, and press them at 20 MPa. During the test, the detector slit is 3 nm. In order to avoid interference between linear dichroism and circular dichroism during the measurement process, the sample cell was rotated 90° for testing.
[0065] From the test results, it can be seen that Figure 8 (a) The compound shown [(PN)2Cu2(dca)Cl] n 1 basically shows a negative Condon effect, and exhibits a certain degree of circular dichroism in the range of 300nm to 500nm. Figure 8 (b) shows that in the range of 300nm to 500nm, the compound [(PN)2Cu2(dca)Cl] n 1 also exhibits a unique linear dichroism, which corresponds one-to-one with the UV-visible absorption spectrum (e.g. Figure 8 (d)). In addition, during the test, Figure 8 The detection voltage value of the detector shown in (c) is always less than 800V, indicating that the test results are true and reliable. Based on this, it can be basically determined that the compound [(PN)2Cu2(dca)Cl] n1 exhibits both circular dichroism and linear dichroism, and the source of its chirality is closely related to the chromophores inside the material.
[0066] After rotating the test sample 90 degrees, it can be seen that Fig. 9 The compound shown [(PN)2Cu2(dca)Cl] n 1 still maintains very similar chiral characteristics. It is worth noting that its linear dichroism spectrum is relatively more obvious in the range of 300-480nm. This may be due to the one-dimensional chain molecular structure of the compound (such as Figure 2 As shown in Figure 2, in this measurement state, the difference between the polarized light parallel to and perpendicular to the molecular orientation direction is more obvious. This result once again illustrates that the compound [(PN)2Cu2(dca)Cl] n 1 exhibits both circular dichroism and linear dichroism.
[0067] It is worth mentioning that the compound [(PN)2Cu2(dca)Cl] n 1 showed excellent linear polarization. The compound [(PN)2Cu2(dca)Cl] was also made using FLS1000. n 1 A series of linearly polarized emission spectra (such as Fig.10 , Fig.11 By rotating the angle of the linear polarizer between the test sample and the detector, the compound [(PN)2Cu2(dca)Cl] can be obtained. n 1 Changes in emission intensity, emission position and emission peak shape between 0 and 180°.
[0068] It can be observed that Fig.12 As shown in the figure, as the polarizer rotates from 0° to 90° and then to 180°, the compound [(PN)2Cu2(dca)Cl] n The fluorescence emission intensity of 1 first gradually decreases and then gradually increases. This trend shows that near 0°, the compound [(PN)2Cu2(dca)Cl] n 1 is parallel to the optical axis of the linear polarizer. In this case, a large number of fluorescent emission photons can pass through the optical axis smoothly, so that the fluorescence intensity reaches the maximum value. As the linear polarizer rotates, the compound [(PN)2Cu2(dca)Cl] n The parallel relationship between the fluorescence emission direction of 1 and the optical axis gradually weakens, causing some fluorescent photons to be blocked by the optical axis of the polarizer and unable to reach the detector smoothly. This weakens the fluorescence emission intensity. When the rotation angle of the polarizer reaches 90°, the compound [(PN)2Cu2(dca)Cl] nThe fluorescence emission intensity of 1 is at its lowest point, at which point the polarizer almost completely blocks the emitted photons. As the rotation angle continues from 90° to 180°, the polarizer begins to allow previously blocked photons to reach the detector at different angles. At 180°, the compound [(PN)2Cu2(dca)Cl] n The fluorescence emission direction of 1 is antiparallel to the optical axis of the polarizer. At this time, a large number of fluorescent photons can pass through the optical axis smoothly, so that the fluorescence intensity reaches the maximum again. This phenomenon shows that the compound [(PN)2Cu2(dca)Cl] n The fluorescence emission characteristics of 1 have a significant dependence on the angle change of the polarizer, reflecting its highly linearly polarized nature. Such behavior not only provides important clues for understanding the luminescence mechanism of this compound, but also lays the foundation for its potential application in optoelectronic devices. For example, in polarization-based optical devices, this property can be used to improve the quality and contrast of optical signals. In addition, in-depth research on this phenomenon will also help to reveal the electronic structure and interactions within the compound, thereby providing a theoretical basis for the design of new optical materials. Therefore, the compound [(PN)2Cu2(dca)Cl] n 1 shows broad prospects in future optical applications and is expected to promote the development of optoelectronic technology.
[0069] By calculating the emission dichroic ratio (Imax / Imin), the compound [(PN)2Cu2(dca)Cl] can be obtained. n 1 has a polarization ratio δ of 1.77. This value indicates that the compound [(PN)2Cu2(dca)Cl] n 1 exhibits significant linear polarization characteristics when emitting light, especially at a specific polarization angle θ. When θ is approximately 0° and 180°, the luminescence intensity reaches a maximum value Imax, reflecting the compound's good photon emission ability in these directions. When θ is approximately 90°, the luminescence intensity drops to a minimum value Imin, further emphasizing its high sensitivity to polarization angle. This strong angular dependence is not only due to the compound [(PN)2Cu2(dca)Cl] n 1The excellent linear polarization luminescence characteristics also provide an important theoretical basis for its practical application. This characteristic makes it have great application potential in optical devices, especially in display technology that requires high contrast and clarity. For example, the use of materials with strong linear polarization characteristics can improve the visual effect and color saturation of liquid crystal displays. More importantly, Fig.12As shown in the figure, the relationship between the luminescence intensity and the polarization angle θ can be accurately fitted as a sin2θ function, i.e., a cos2θ function. This mathematical relationship not only shows the periodic characteristics of the luminescence behavior, but also implies the existence of a highly ordered crystal structure and spin selectivity inside the compound. Such a structure can effectively limit the distribution of excited states, so that photon emission is enhanced in a specific direction, thereby producing strong linearly polarized luminescence.
[0070] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A right-handed helical chiral organometallic halide, characterized in that: The chemical formula of the right-handed helical chiral organometallic halide is [(PN)2Cu2(dca)X] n ; Wherein, PN is an asymmetric organic phosphine ligand, dca is a dicyanamide anion, and X is a halogen ion.
2. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The right-handed helical chiral organic metal halide is obtained by self-assembly of an asymmetric organic phosphine ligand, a dicyanamide salt and a cuprous halide in a hot saturated solvent.
3. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The right-handed helical chiral organometallic halide has an orthorhombic crystal structure, a space group of Pna21, and a one-dimensional chain-like helical chiral structure.
4. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: In the crystal structure of the right-handed helical chiral organometallic halide, Cu1 and Cu2 ions are bridged by halogen ions to form a binuclear metal cluster, and Cu ions are coordinated with asymmetric organophosphine ligands and dicyanamide anions to form a distorted trigonal bipyramidal structure.
5. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The X is selected from Cl - Br - ,I - At least one halogen ion.
6. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The right-handed helical chiral organic metal halide has a linearly polarized luminescence characteristic, and a polarization ratio is 1.
77.
7. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The right-handed helical chiral organic metal halide has an emission wavelength of 575nm to 625nm within the range of an excitation wavelength of 250nm to 420nm, and exhibits a red shift as the excitation wavelength increases.
8. The right-handed helical chiral organometallic halide according to claim 1, characterized in that: The right-handed helical chiral organic metal halide has a thermal weight loss temperature greater than or equal to 372° C., and a phase transition temperature greater than or equal to 219° C.
9. The method for preparing the right-handed helical chiral organometallic halide according to any one of claims 1 to 8, characterized in that: The steps include: Adding a mixture containing an asymmetric organic phosphine ligand, a dicyanamide salt, and a cuprous halide to a hot saturated solvent and mixing them uniformly, dissolving them by heating, cooling them, and then precipitating and self-assembling to obtain the right-handed helical chiral organic metal halide; Preferably, the asymmetric organic phosphine ligand is selected from diphenyl-2-pyridylphosphine ligand; Preferably, the dicyanamide salt is selected from sodium dicyanamide; Preferably, the cuprous halide is selected from at least one of cuprous chloride, cuprous bromide, and cuprous iodide; Preferably, the hot saturated solvent is selected from a mixed solution of DMF and acetonitrile; Preferably, the molar ratio of the organic phosphine ligand, dicyanamide salt, and cuprous halide is 1:(0.4-0.6):(0.8-1.2); Preferably, the conditions for heating and dissolving include: under vacuum or anaerobic conditions, the heating temperature is 1120-130° C., and the heating time is 30-60 min; Preferably, the self-assembly time is 18 to 36 hours.
10. Application of the right-handed helical chiral organometallic halide according to any one of claims 1 to 8 as a linearly polarized luminescent material in optoelectronic fields such as high-end anti-counterfeiting, quantum communication and photonic devices.
Citation Information
Patent Citations
Metal halide material capable of emitting blue circularly polarized light as well as preparation method and application of metal halide material
CN118598914A
Optically active diaminophosphine-coordinated transition metal complex
JP2000154195A